Self Nanoemulsifying Drug Delivery System: A Comrhensive Review - Anuja, Gawai G.; Sandip, Atram C.; Rupali, Sable P.; Vrunda, Rajput J.; Subhod, Urkunde A. (Asian Journal of Pharmaceutical Research and Development, 2024)
SNEDDS is also important to create a wide interface for distributing the hydrophobic drug between the oil and aqueous phase, increasing the overall bioavailability of the drug.This process can be stabilized using emulsifiers that reduce interfacial tension.Self-nanoemulsified dosage forms can improve the oral bioavailability of biopharmaceutical class II and IV drugs, The potential mechanism by which SNEDDS increases oral bioavailability.Oral administration of peptides due to proteins is a very difficult task due to poor water quality, poor permeability and tolerance of intestinal environmental stability. Many strategies are being investigated to increase the oral absorption of protein. Recently, evaluated the ability of SNEDDS to improve the oral bioavailability of β-lactamase, a model protein. SNEDDS to the solid state can reduce chemical degradation, but in many cases does not eliminate it. Therefore, it is important to identify microenvironment modification strategies to improve the stability of pH-sensitive drugs.